2015
DOI: 10.1093/abbs/gmv066
|View full text |Cite
|
Sign up to set email alerts
|

<italic>In vitro</italic> effects of phenytoin and DAPT on MDA-MB-231 breast cancer cells

Abstract: Voltage-gated sodium channel (VGSC) activity enhances cell behaviors related to metastasis, such as motility, invasion, and oncogene expression. Neonatal alternative splice form of Nav1.5 isoform is expressed in metastatic breast cancers. Furthermore, aberrant Notch signaling pathway can induce oncogenesis and may promote the progression of breast cancers. In this study, we aimed to analyze the effect of the nNav1.5 inhibitor phenytoin and Notch signal inhibitor N-[N-(3,5-difluorophenacetyl)-L-alanyl]-S-phenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
3
1
Order By: Relevance
“…Although a number of previous studies demonstrated that these five signaling inhibitors exert inhibitory effects on TNBC in animal models and in clinical trials (49)(50)(51)(52)(53), in the present study, it was demonstrated that all five signaling inhibitors suppressed stemness of BCSCs in extensive aspects, including proliferation, invasion, apoptosis, self-renewal, mammosphere formation and tumorigenesis. In addition, the inhibition efficacy of these five inhibitors against TNBC was compared.…”
Section: Discussioncontrasting
confidence: 58%
“…Although a number of previous studies demonstrated that these five signaling inhibitors exert inhibitory effects on TNBC in animal models and in clinical trials (49)(50)(51)(52)(53), in the present study, it was demonstrated that all five signaling inhibitors suppressed stemness of BCSCs in extensive aspects, including proliferation, invasion, apoptosis, self-renewal, mammosphere formation and tumorigenesis. In addition, the inhibition efficacy of these five inhibitors against TNBC was compared.…”
Section: Discussioncontrasting
confidence: 58%
“…Notch signaling inhibition resulted in the attenuation of cancer cell invasion and migration (55,56,59). In this regard, DAPT significantly inhibited breast cancer cell migration in an in vitro wound healing assay.…”
Section: Discussionmentioning
confidence: 98%
“…This cell line is the most studied triple-negative breast cancer cell line, which has a significant practical value. For example, MDA-MB-231 cells have been extensively used for cancer metastasis [ 42 , 43 ] and drug resistance studies [ 44 , 45 ]. During this process, QFeNPs were used as the loading NPs for several reasons.…”
Section: Discussionmentioning
confidence: 99%